A new otter of giant size, Siamogale melilutra sp. nov. (Lutrinae: Mustelidae: Carnivora), from the latest Miocene Shuitangba site in north-eastern Yunnan, south-western China, and a total-evidence phylogeny of lutrines. (2nd January 2018) - Wang, Xiaoming; Grohé, Camille; Su, Denise F.; White, Stuart C.; Ji, Xueping; Kelley, Jay; Jablonski, Nina G.; Deng, Tao; You, Youshan; Yang, Xin
Abstract : Otters (subfamily Lutrinae) are semi-aquatic predators in the family Mustelidae. Modern otters have a worldwide distribution but their fossil record is poor, often consisting of fragmentary jaws and teeth. Multiple lineages have developed bunodont dentitions with enlargements of molars, usually for cracking molluscs or other hard foods. Some lineages have evolved badger-like teeth and, as a result, were often confused with melines (Old World badger clade). Siamogale thailandica Ginsburg, Invagat, & Tassy, 1983 from the middle Miocene basin of Mae Moh in northern Thailand is one such species, whose fragmentary dental remains have thus far impeded our understanding. A new species of fossil otter, Siamogale melilutra sp. nov., represented by a nearly complete cranium, mandible and partial skeletons of at least three individuals, was recovered from the latest Miocene (∼6.2 Ma) lignite beds of the Shuitangba Site in north-eastern Yunnan Province, south-western China. Computed tomography (CT) restoration of the crushed skull reveals a combination of otter-like and badger-like cranial and dental characteristics. The new species belongs to the Lutrinae because of its possession of a large infraorbital canal and ventral expansion of the mastoid process, among other traits. A distally expanded M1, however, gives a badger-like appearance. In overall morphology the Shuitangba otter is closest to Siamogale thailandica . A previously described jaw (' Lutra ' aonychoides ) from the early Pliocene of the Yushe Basin in north China is also here referred to S. melilutra . No previous attempt has been made to provide a global phylogenetic framework for otters. We present the first combined morphological and molecular (nuclear and mitochondrial DNAs) character matrices of five extant ( Pteronura, Lontra, Enhydra, Aonyx, Lutra ) and eight extinct genera ( Tyrrhenolutra, Paralutra, Paludolutra, Enhydritherium, Siamogale, Vishnuonyx, Sivaonyx, Enhydriodon ) to better understand the evolution of bunodont otters. Parsimony and Bayesian analyses consistently recover an eastern Asian clade that includes forms from Shuitangba, Yushe and Mae Moh, all of which are referred to Siamogale . http://zoobank.org/urn:lsid:zoobank.org:pub:5C637018-0772-4C78-AA4B-783B71085D9D